1997
DOI: 10.1056/nejm199704103361502
|View full text |Cite
|
Sign up to set email alerts
|

Fish Consumption and the 30-Year Risk of Fatal Myocardial Infarction

Abstract: These data show an inverse association between fish consumption and death from coronary heart disease, especially nonsudden death from myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
415
5
18

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 785 publications
(444 citation statements)
references
References 36 publications
6
415
5
18
Order By: Relevance
“…Validation studies have shown that the intake of ®sh was higher when reported with the questionnaire than with dietary records (108 vs 75 gad) (Nes et al, 1992) and 48 h recall (71 vs 64 gad) . The ®sh intake in our survey was higher than reported in national dietary surveys in the Netherlands (approximately 10 gad) (Hulshof et al, 1991), Denmark (24 gad) (Andersen et al, 1996), Sweden (30 gad) (Becker, 1994), as well as in large prospective surveys in the Netherlands (Kromhout et al, 1985) and USA (Daviglus et al, 1997), and secondary prevention trials in UK (Burr et al, 1989). However, the ®sh intake was lower than reported in national surveys in Iceland (73 gad) and Japan (approximately 90 gad) (World Health Organization, 1990).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Validation studies have shown that the intake of ®sh was higher when reported with the questionnaire than with dietary records (108 vs 75 gad) (Nes et al, 1992) and 48 h recall (71 vs 64 gad) . The ®sh intake in our survey was higher than reported in national dietary surveys in the Netherlands (approximately 10 gad) (Hulshof et al, 1991), Denmark (24 gad) (Andersen et al, 1996), Sweden (30 gad) (Becker, 1994), as well as in large prospective surveys in the Netherlands (Kromhout et al, 1985) and USA (Daviglus et al, 1997), and secondary prevention trials in UK (Burr et al, 1989). However, the ®sh intake was lower than reported in national surveys in Iceland (73 gad) and Japan (approximately 90 gad) (World Health Organization, 1990).…”
Section: Discussioncontrasting
confidence: 55%
“…The main sources for these fatty acids are marine oils and ®sh. In some studies the intake of marine oils (Nestel, 1987) and ®sh (Kromhout et al, 1985;Daviglus et al, 1997) are associated with reduced risk for coronary heart disease (CHD), although this has not been observed in other studies (Vollset et al, 1985;Morris et al, 1995;Ascherio et al, 1995). Of four prospective studies reporting intake of n-3 fatty acids from ®sh, one found an inverse association (Dolecek, 1992), another reported a positive association (Pietinen et al, 1997) and the others reported no signi®cant association to CHD (Morris et al, 1995;Ascherio et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…What is the optimal intake (amount and frequency) of ®sh? Several prospective observational studies and a randomised factorial trial showed that one serving of ®sh weekly may decrease the risk of fatal CHD by approximately 40% relative to no ®sh (Burr et al, 1989;Ascherio et al, 1995;Kromhout et al, 1995;Gillum et al, 1996;Daviglus et al, 1997). Higher intakes did not provide greater protection.…”
Section: Fish and Healthmentioning
confidence: 99%
“…A growing body of literature supports a protective role of fish intake and of essential dietary long-chain polyunsaturated fatty acids in cardiovascular disease (Dolecek & Granditis, 1991;Ascherio et al, 1995;Daviglus et al, 1997;Hopper et al, 1999;Oomen et al, 2000;Rissanen et al, 2000;Hallgren et al, 2001;Iso et al, 2001;Yuan et al, 2001) including a reduction of the risk of sudden cardiac death (Siscovick et al, 1995;Albert et al, 1998). There are several potential mechanisms for this protection including antithrombotic (Kristensen et al, 1989;Prisco et al, 1995) and anti-arrhythmic effects (Marchioli et al, 2002), decreased heart rate variability (Christensen et al, 1997) and resting blood pressure (Knapp, 1989), decreased serum LDL cholesterol and triglyceride concentrations (Agren et al, 1996) and increased insulin sensitivity (Torjesen et al, 1997;Mori et al, 1999).…”
Section: Introductionmentioning
confidence: 99%